Young people, young adults and binge drinking - LA FAUCI, V. (J Prev Med Hyg, 2019)
INTRODUCTION AND PURPOSE: The consumption of alcohol among young people and young adults has undergone, in recent decades, a sharp upsurge with the increasingly frequent intake of large quantities of alcohol. The aim of our study was to investigate socio-demographic, economic and behavioural factors that have a major impact on the voluntary alcohol habit in young people. METHODS: The survey was conducted via administration of an anonymous questionnaire based on “the WHO Alcohol Use Disorders Identification Test”, disseminated on-line, to young people and young adults (aged 18 to 35). RESULTS: We examined a sample of 365 subjects. Consumption of wine and beer were predominant followed by super-alcohol mixes. We found correlations between alcohol use and the following variables: marital status (p < 0.001), parental education (mother p < 0.05; father p < 0.001), income level (p < 0.05), physical activity (p < 0.05) and voluptuous habits (smoke and coffee: p < 0.001.The 5% of men and 1% of women had car accidents during the previous year due to alcohol use and 15% said they did not remember what happened in an alcoholic evening once or twice a month. CONCLUSIONS: The phenomenon of alcohol consummation is deeply ingrained in our reality, with dangerous episodes of binge drinking in young adults with a higher prevalence in the female sex.